Cisco CCNP ENCOR v1.1 (350-401) Cert Prep: 2 Network Management, Security, and Automation. - Wallace, Kevin (linkedin.com, 2023)
Prepare for the last three domains of the Cisco CCNP ENCOR (350-401) certification exam: Network Management, Security, and Automation.